Comparative evaluation of six chromogenic media for presumptive yeast identification. Issue 12 (29th June 2017) - Vecchione, Alessandra; Florio, Walter; Celandroni, Francesco; Barnini, Simona; Lupetti, Antonella; Ghelardi, Emilia
Abstract : Aims: The present study was undertaken to evaluate the discrimination ability of six chromogenic media in presumptive yeast identification. Methods: We analysed 108 clinical isolates and reference strains belonging to eight different species: Candida albicans, Candida dubliniensis, Candida tropicalis, Candida krusei, Candida glabrata, Candida parapsilosis, Candida lusitaniae and Trichosporon mucoides . Results: C. albicans, C. tropicalis and C. krusei could be distinguished from one another in all the tested chromogenic media, as predicted by the manufacturers. In addition, C. albicans could be distinguished from C. dubliniensis on BBL CHROMagar Candida, Kima CHROMagar Candida and Brilliance Candida, and C. parapsilosis could be identified on CHROMATIC Candida agar, CHROMOGENIC Candida agar, and Brilliance Candida agar. Conclusions: Brilliance Candida provided the widest discrimination ability, being able to discriminate five out of the seven Candida species tested. Interestingly, C. tropicalis and C. krusei could be already distinguished from each other after 24 hours of incubation.